2002
DOI: 10.1080/02652040110065468
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of linoleic acid encapsulated with gum arabic or maltodextrin by spray-drying

Abstract: Linoleic acid was emulsified with gum arabic or maltodextrin at various weight ratios of the acid to the polysaccharide in the presence or absence of a small-molecule emulsifier. The emulsions were spray-dried to produce microcapsules. Emulsions prepared with gum arabic were smaller in droplet size and more stable than those prepared with maltodextrin, and linoleic acid in a gum arabic-based microcapsule was also most resistant to oxidation than that in a maltodextrin-based microcapsule. Although the oil dropl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
1
6

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(89 citation statements)
references
References 13 publications
6
76
1
6
Order By: Relevance
“…Hal ini ditandai dengan besarnya nilai surface oil seperti yang terlihat pada Gambar 2. Hasil yang sama juga didapat dari penelitian yang dilakukan oleh Minemoto et al (2002), dimana berat inti yang meningkat membuat nilai efisiensi enkapsulasi menurun. Hal tersebut disebabkan oleh jumlah gum arabic yang digunakan sebagai penyalut tidak cukup untuk membungkus seluruh minyak, sehingga nilai efisiensi enkapsulasi menjadi menurun.…”
Section: Efisiensi Enkapsulasi Oleoresin Jahe Merahunclassified
“…Hal ini ditandai dengan besarnya nilai surface oil seperti yang terlihat pada Gambar 2. Hasil yang sama juga didapat dari penelitian yang dilakukan oleh Minemoto et al (2002), dimana berat inti yang meningkat membuat nilai efisiensi enkapsulasi menurun. Hal tersebut disebabkan oleh jumlah gum arabic yang digunakan sebagai penyalut tidak cukup untuk membungkus seluruh minyak, sehingga nilai efisiensi enkapsulasi menjadi menurun.…”
Section: Efisiensi Enkapsulasi Oleoresin Jahe Merahunclassified
“…The amount of unoxidized linoleic acid within the microcapsules was determined by gas chromatography according to our previously reported procedure. 9) Stability of the emulsions. A wall material (2.25 g) was dissolved in 15 ml of distilled water, and 0.45 g of linoleic acid was added to the solution.…”
Section: Methodsmentioning
confidence: 99%
“…Factors affecting the oxidative stability of the encapsulated lipid, such as the type of polyunsaturated fatty acid, kind of wall material, and weight ratio of the lipid to wall material, have been examined [5][6][7][8][9][10] . We reported that the oxidation proceeded more slowly for the linoleic acid encapsulated with maltodextrin in smaller oildroplets 7,8) . In these reports, the oil-droplet sizes in emulsions were on the orders of submicrometers or micrometers.…”
Section: Introductionmentioning
confidence: 99%
“…This is a feature of the oxidation of encapsulated unsaturated fatty acid. 7,8) The change with time of the fraction of unoxidized methyl linoleate in the microcapsule, Y, was expressed by the following modified Weibull equation: (1) where Y ∞ is the unoxidized oil fraction at which the oxidation leveled off or practically ceased, t is the storage time, k is a rate constant and n is a shape constant. The Y ∞ value was evaluated by averaging the Y values for long storage periods, and the parameters, k and n, were then determined to best-fit the experimental results to using the Solver of Microsoft Excel for Windows.…”
mentioning
confidence: 99%